The Epidemiology of Circulating Rotavirus Associated with Diarrhea in Egyptian Kids and Calves: A Review - Ahmed H. Ghonaim; Mai G. Hopo; Noha H. Ghonaim; Yunbo Jiang; Qigai He; Wentao Li (Zoonoses, 2023)
Acute gastroenteritis (AGE) induced by rotavirus has been a major disease burden in Egypt since 1981 when rotavirus was first reported in humans and calves. Genome segmentation facilitates the emergence of new virus serotypes, which allows reassortment during mixed infections, and is a characteristic feature of the family Reoviridae to which rotavirus belongs. The rotavirus genome involves 11 double-stranded RNA gene segments encoding 6 non-structural (NSP1–6) and 6 structural (VP1–4, VP6, VP7) proteins. Rotavirus A has a zoonotic potential associated with diarrhea. The primary strategy for prevention and control of bovine and human rotavirus infections is vaccination; however, routine rotavirus vaccination has not been implemented in the National Immunization Program. We evaluated studies published over the last 30 years that pertained to the epidemiology of circulating rotavirus genotypes among children, calves, and environmental samples in Egypt. The analysis revealed a rotavirus prevalence of 15%–100%, with diarrhea occurring throughout the year, but generally peaking during the cold months. G1 was the predominant genotype in children, followed by G2, G3, G4, G8, G9, and G12 throughout the study duration. Mixed infections were also detected. G6 was the predominant genotype in calves, followed by G10. There are still gaps in knowledge regarding molecular data of rotavirus infections in humans, animals, and environmental samples in Egypt, as well as the zoonotic potential of rotavirus disease. Therefore, it is critical to continue rotavirus surveillance in Egypt to further understand the epidemiology of rotavirus infections and the emerging new genotypes.